مدى تحقيق مشروع تطوير مناهج العلوم الطبيعية لأهدافه من وجهة نظر المشرفات التربويات و معلمات العلوم بالمملكة العربية السعودية - عمر سعاد جعفر (Journal of Faculty of Education, 2021)
This study aims to evaluate the developed science curriculum implemented in intermediate and secondary schools, which has been developed by accommodation of global foreign scientific series resembled by Mc Graw Hill series through dealing with the data collected as feed-back from supervisors and teachers of science at intermediate and secondary schools (women) in KSA. (At Najran regoin). This study tries to give an answer to the main question: To what extent could the developed science curriculum succeed in achieving the objectives of the project of development? A number of sub-questions arise from this main question. The Researcher used the descriptive analytical research methodology. Tools of the study were a questionnaire to be answered by teachers and supervisors of science in intermediate and secondary schools at Najran rejoin. The data collected was analyzed by using SPSS package. The results achieved were as follows: - Supervisors and teachers accept the idea of development of science curriculum by accommodation. - They agree about the effectiveness of the developed science curriculum in achieving the objectives of the project of of science curriculum development in line with global standards. The researcher concluded with the following recommendations: - Greater care should be given to the laboratories and equipments. - Ministry of education should support and motivate teacher’s professional activities.